3D Kinematics - Haslwanter, Thomas (Springer International Publishing, 2018)
This book presents an introduction to the analysis of general movements in 3D space, especially for movements of the human body. It is based on the lecture notes of a class on 3D Kinematics, which the author has been holding in the Master Degree Program of his home institution, the University of Applied Sciences Upper Austria. The lecture introduces the mathematics underlying the measurement and analysis of 3D movements. The target audience primarily comprises research experts in the field, but the book may also be beneficial for graduate students alike. .